Patients’ experiences with virtual group gut-directed hypnotherapy: A qualitative study - Gerson, Jessica; Tawde, Prianca; Ghiasian, Ghoncheh; Salwen-Deremer, Jessica K. (Frontiers in Medicine, 2023)
Background Hypnotherapy is a useful treatment for a variety of gastrointestinal conditions. While there is strong evidence for delivering other treatments virtually and in groups, there is no research thus far on delivering hypnotherapy in this format. Given the growth of both psychogastroenterology and telehealth, these methods should be explored as they have great potential for increasing access and cost-effectiveness of intervention. Aims This qualitative study was developed to help understand patients experiences in virtual, group-based, gut-directed hypnotherapy (GDH) in two different institutions. Methods Authors developed a qualitative interview with the assistance of two patient partners and then recruited patients from New York University and Dartmouth Health to participate. Interviews were completed one-on-one with patients who started and then completed GDH (≥5 visits) and who did not complete GDH (≤3 visits). Data were coded and then analyzed using thematic analysis. Results Twenty-one patients from NYU and Dartmouth participated in qualitative interviews. Broadly, patients reported coming to GDH because they believed in the importance of the mind-body connection or were desperate for treatment. Regardless of why patients came to GDH, they generally reported positive outcomes for GI symptoms and for other physical and mental health conditions. Most patients appreciated the group and virtual formats, though some concerns about inflexible schedules and lack of anonymity were voiced. Despite these concerns, there was broad support for virtual, group-based GDH and general excitement for behavioral health programming. Conclusion Virtual, group-based GDH is an acceptable treatment for patients from rural and urban settings. Given the possible improvements in access and cost-effectiveness that this treatment modality can provide, GI practices may want to consider it in lieu of or in addition to the traditional one-on-one treatment format. Barriers and facilitators and recommendations for practice are discussed.